Practical lessons for your financial life : collections. - Glassman, Saly A., 1958- ([FT Press], 2012)
A brand new collection of Saly A. Glassman's powerful common-sense insights into personal financial security Transform "fairy tale" stories into real financial security: an extraordinary collection of insights and how-tos from award-winning financial advisor Saly A. Glassman, including her breakthrough book, It's About More Than the Money! Now available as a collection, Saly A. Glassman's eBook Shorts teach no-nonsense financial lessons that everyone needs to learn. You'll experience a quick, easy-to-read format that gets the point across fast ! In Mirror, Mirror on the Wall: Personal Reflection for Sound Investing and Self-Improvement, Saly A. Glassman helps you seek your "true reflection" and understand three crucial realities about money. Discover how to build a happier, wealthier, and more fulfilling life. The Princess and the Frog: Managing Your Word and Your Investments helps you fully understand the financial "deals" you're making, comprehend their consequences, and proceed with clarity and integrity. In Three Wishes: Why Wishing Is No Substitute for Financial Planning, Glassman explains why financial planning is even more important than you realize. Three Wishes clearly illuminates the consequences of poor planning and foolish goals and shows how to keep it from happening to you. In The Emperor's New Clothes: Investment Strategies That Help Keep You Covered, Glassman shows how to recognize when you're deceiving yourself. You'll learn how to manage greed and fear, avoid getting enticed by "magic bullet" solutions like gold or real estate, implement safeguards that reduce your risks, gain courage to face the truth, and use that knowledge to build your potential for long-term financial security! In addition to these four eBook Shorts, this exclusive Safari edition includes Glassman's highly praised book It's About More Than the Money: Investment Wisdom for Building a Better Life. Acomplete plan for regaining control over your financial life, this book brings together 21 fundamental investment principles. Glassman offers real case studies and guides you through putting them to work. It'll help you make wiser, better financial decisions--whatever your goals, whatever your age, and whatever the economy does next!